Establishing Good Agricultural Practices for the Use of Chlormequat Chloride in Grapes to Improve Vine Vigour, Fruitfulness, and Revision of MRL - Deshmukh, Nishant; Ekatpure, S.; Taynath, Bharat; Appaso; Sahadev; Sharad; kaushik (South African Journal of Enology and Viticulture, 2025)
Chlormequat chloride (CCC), a gibberellin biosynthesis inhibitor, is widely used in vineyards to regulate vegetative growth and promote berry elongation in grapes. However, its low maximum residue limit (MRL) of 0.05 mg/kg poses challenges for grape exports due to stringent food safety regulations. This study aimed to enhance the maximum residue level (MRL) and revise good agricultural practices (GAP) for CCC application to manage grapevine vigour, enhance fruitfulness, and generate residue data for MRL revision and risk assessment. Field trials were conducted across three locations in Maharashtra, India, during the 2021-2022 and 2022-2023 grape seasons. CCC was applied at rates of 250–2000 g/ha at various growth stages of Thompson Seedless grapevines. Residue analysis using liquid chromatography tandem mass spectrometry (LC-MS/MS) demonstrated that revised CCC treatments significantly reduced shoot length and internodal growth while increasing cane diameter compared to current GAP recommendations. The proposed GAP includes foliar applications of CCC at 1500 g/ha (11-12 leaf stage) and 2000 g/ha (15-16 leaf stage) after foundation pruning, followed by 250 g/ha (3-5 leaf stage) after fruit pruning. This regimen achieved a maximum residue of 0.2 mg/kg, supporting its safety for consumer health. The study will allow growers to achieve higher yields of grapes with better and safer quality subject to revision of the national MRL to 0.2 mg/kg without causing any appreciable health risks to consumers.